2020
DOI: 10.21203/rs.3.rs-44844/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated serum triglyceride predicts recurrence of colorectal polyps in patients with advanced adenomas

Abstract: Background: Recurrence of colorectal polyps is common and impacted by various factors. This study was performed to explore the association between lipid profiles and recurrence of colorectal polyps.Methods: This study retrospectively analyzed the lipid profiles of 435 patients who underwent colonoscopy with removal of colorectal polyps and assessed recurrence of polyps by follow-up colonoscopy. Multivariate regression logistic analysis was used to evaluate the association between lipid profiles and polyp recur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Another mechanism is that dyslipidemia creates a tumorigenic environment by increasing levels of interleukin-6, tumor necrosis factor-α, and other in ammatory cytokines 33 . Finally, Boying Liu et al suggested that TG may affect polyp recurrence by increasing the proliferative capacity of cancer stem cells or stimulating signaling pathways that promote cell invasion 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism is that dyslipidemia creates a tumorigenic environment by increasing levels of interleukin-6, tumor necrosis factor-α, and other in ammatory cytokines 33 . Finally, Boying Liu et al suggested that TG may affect polyp recurrence by increasing the proliferative capacity of cancer stem cells or stimulating signaling pathways that promote cell invasion 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Identifying non-invasive markers of polyp recurrence risk could help identify at-risk patients. Elevated triglyceride levels in serum are an independent risk factor for polyp recurrence in patients with advanced adenomas 13 . Long-term lipid stimulation suppresses anti-tumor immune responses, facilitating colorectal tumorigenesis and distant metastasis, and suppresses immune in ltrating cell function in the tumor microenvironment, thereby accelerating tumor progression 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The serum lipid pro les were examined using commercial kits following manufacture's instruction as previously described [19]. Fasting blood sample was collected from each participant within 24 hour after admission.…”
Section: Serum Lipid Pro Les Testingmentioning
confidence: 99%